Anion Exchange Membrane Capacitive Deionization Cells. Issue 9 (1st July 2017) - Omosebi, Ayokunle; Gao, Xin; Holubowitch, Nicolas; Li, Zhiao; Landon, James; Liu, Kunlei
Abstract : The electrochemical response of capacitive deionization (CDI) employing a single anion exchange membrane (AEM-CDI) is contrasted to conventional two-membrane CDI (MCDI) formed with complementary anion and cation exchange membranes. Pristine activated carbon cloth electrodes that possess native positive surface charge in solution were used as both anode (positive electrode) and cathode (negative electrode) in these cells. In a separate set of tests to investigate the impact of surface charge modification on deionization responses, the single and dual membrane cells were formed with asymmetric electrodes (AEM-aCDI and aMCDI) consisting of nitric acid oxidized electrodes that possess negative surface charge as the cathode material, while pristine carbon cloth was retained as the anode material. Operating at 1.2 V, salt adsorption capacities are ∼1.3, 9.9, and 16.6, and 17.3 mg NaCl g −1 electrode for the AEM-CDI, MCDI, AEM-aCDI, and aMCDI, respectively. The diminished performance of AEM-CDI is attributed to charge expulsion and enhanced parasitic electrochemical reactions at the unprotected cathode that reduce the charge efficiency. In contrast, for AEM-aCDI, a treated cathode enhances surface charge effects to match aMCDI performance with half the membrane requirement.